Spatial acoustic-based reverberation simulation as a representable reality in the internet era - Musib, Ahmad Faudzi; Chow, Ow Wei (University of Visual and Performing Arts (UVPA), 2019)
The emerging internet has indicated that modern human civilisation highly attributed by the Internet of Things (IoT) which is characterised by the enormous ‘big data’ captured through device sensors and mediated communication platforms. Meanwhile, there is an increasing keenness in exploring the inception of reality in the Internet Era as the scholarly discussion on how IoT potentially changes the patterns of seeing, considering and representing the reality is in high demands at present. This paper proposes workable means of representable reality by generating and re-generating acoustic data that reflect spatial properties of a designated environment through technical formulation of reverberation simulation. It also considers possible conditions of such representation, especially the process control through real-time accessibility of data directly collected from machine–machine communication via sensors, IP addresses and network connectivity. The methodological outcome of this simulation offers a result that a captured instrumental sound event can be played as if in a contextualised space, which in the past has to be physically constructed to accommodate a certain relevant technology in audio recording. With a new method that can feasibly rework any acoustic phenomenon, a physical construction of the desirable contextualised space is no longer required. Moreover, digital data captured from various geographical locations can be mapped in an internet-based platform of potential cartographic or site navigation in order to facilitate remote users in experiencing a representable reality. This paper also discusses possible issues arising from the simulation framework and the impacts of IoT, which are concisely reviewed, as well as various approaches in the sense-making of contemporary sound studies.